Δικαιοσυγκριτική επισκόπηση της ιατρικής ευθύνης στο ελληνικό και αγγλοσαξωνικό δίκαιο - Λαμπρόπουλος, Γεώργιος Βασιλείου (Πανεπιστήμιο Πελοποννήσου, 2012)
Although the law of professional malpractice extends to a wide range of specialized, professional activities, in public mind, malpractice is most frequently associated with medical professions. Medical error is an everyday phenomenon. This paper presents in detail the concept of medical malpractice, beginning from the fundamental concept “medical error” and its legal consequences. At the same time, it analyzes the legal framework (Greek Civil Code and article 8 of Law 2251/1994) on the grounds of which patients or even third parties may claim compensation for damages (actual and potential) caused by such doctors’ willful misconduct or negligence (gross or simple). Furthermore, as far as the legal part is concerned, special topics, such as the case of “wrongful life” or “wrongful birth”, the hospitals’ liability, the physicians’ insurance against civil liability and the economic analysis of medical errors are presented in this paper. Lastly, this paper deals with the comparison between the Greek Law and Common Law in regard with the medical malpractice.
Αριθμός Εισαγωγής: 010232-010233 cd
Keywords: Ιατρική δεοντολογία; Ιατρική -- Δίκαιο και νομοθεσία; Ιατρική ευθύνη; Ελληνικό δίκαιο; Αγγλοσαξωνικό δίκαιο; Ιατρικό λάθος